Aminophylline targeting to lung: Optimization of the size and drug loading of albumin microspheres - Tripathi K.P.; Singh J. (My University, 2025)
Aminophylline, a bronchodilator, was considered a suitable drug for targeting to the lung to treat emphysema. Factorial concept was utilized to optimize the size and drug loading of microspheres suitable for targeting. Aminophylline-loaded albumin microspheres were prepared by heat denaturation adjusting the manufacturing variables, namely albumin concentration, drug concentration, water-oil phase ratio and stirring rate at low and high levels. For two levels of the four variables the experimentation was performed in 16 batches. A good yield of well-defined microspheres of the size range, 2-30 μmlm, were obtained from all the batches. The drug loading was found maximum (36.33 per cent) in batch XV of microspheres prepared with low albumin concentration, high drug concentration, low water oil phase ratio and low stirring rate. The least number (13 per cent) of microspheres of batch XV were below 7 μmlm and the remaining 87 per cent were above this size. Considering the payload and size, microspheres of batch XV were found suitable for targeting to the lung. © 1991 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.